Flash‐Lamp Processing of Charge Extraction Layers for Polymer Solar Cells. Issue 28 (4th September 2022) - Sokeng Djoumessi, Aurelien; Madalaimuthu, Jose Prince; Alam, Shahidul; Anand, Aman; Sichwardt, Anastasia; Fischer, Peter; Rösch, Roland; Schubert, Ulrich S.; Hoppe, Harald
Abstract: Thermal annealing (TA) is one of the most used processing techniques for the fabrication of polymer solar cells. The method is not only used to dry solution‐processed films but also for improving the electrical conductivity and the optical absorption of the materials after coating as films. Its use is questionable in combination with high throughput manufacturing techniques such as roll‐to‐roll large‐scale production since annealing times of several minutes already put up high demands on oven lengths. Furthermore, the commonly used flexible substrates are not compatible with high processing temperatures. Therefore, there is a need for more rapid treatment techniques, which do not negatively affect the plastic substrate. Herein, it is successfully demonstrated that flash lamp annealing (FLA) can be a valid alternative to TA. The FLA technique is applied at various pulse durations and thus energy doses to PEDOT:PSS and SnO2 films used as charge extraction layers in conventional and inverted solar cells architectures. In combination with PM6:Y6 photoactive layer, the obtained device's performances are comparable or even better than the devices treated with the classical TA on a hotplate. In terms of energy efficiency, the FLA is clearly more efficient than the TA, even at the size of prototypes. Abstract : Millisecond flash lamp annealing of PEDOT:PSS and SnO2 charge transport layers in polymer solar cells require less energy and provide comparable or better device performances than classical thermal annealing. This is a strategy for reducing polymer solar cell processing time, energy investments, and production costs.